2014
DOI: 10.1371/journal.pone.0092220
|View full text |Cite
|
Sign up to set email alerts
|

Nematode and Arthropod Genomes Provide New Insights into the Evolution of Class 2 B1 GPCRs

Abstract: Nematodes and arthropods are the most speciose animal groups and possess Class 2 B1 G-protein coupled receptors (GPCRs). Existing models of invertebrate Class 2 B1 GPCR evolution are mainly centered on Caenorhabditis elegans and Drosophila melanogaster and a few other nematode and arthropod representatives. The present study reevaluates the evolution of metazoan Class 2 B1 GPCRs and orthologues by exploring the receptors in several nematode and arthropod genomes and comparing them to the human receptors. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 88 publications
1
13
0
Order By: Relevance
“…Both Bayesian Inference (BI) and Maximum Likelihood (ML) trees had similar branching topologies (Fig. 2, Supplementary Figure 1) and receptor clustering agreed with the previously proposed theories about family B GPCR evolution 43 . The distribution of the mollusc family B GPCRs confirmed that they possess members of the five vertebrate and invertebrate receptor subfamilies.…”
Section: Lophotrochozoan Family B Gpcr Phylogeny Phylogenetic Analyssupporting
confidence: 85%
See 1 more Smart Citation
“…Both Bayesian Inference (BI) and Maximum Likelihood (ML) trees had similar branching topologies (Fig. 2, Supplementary Figure 1) and receptor clustering agreed with the previously proposed theories about family B GPCR evolution 43 . The distribution of the mollusc family B GPCRs confirmed that they possess members of the five vertebrate and invertebrate receptor subfamilies.…”
Section: Lophotrochozoan Family B Gpcr Phylogeny Phylogenetic Analyssupporting
confidence: 85%
“…Characterization of the lophotrochozoan family B GPCRs confirmed that members descended from a unique bilaterian ancestral gene by gene duplication prior to the protostome-deuterostome split 43 . In common with nematodes and arthropods, the clustering of the mollusc and other lophotrochozoan receptors suggests that they probably arose by lineage and species-specific gene duplications driven in part by organismal adaptation to the environment.…”
Section: Discussionmentioning
confidence: 82%
“…Of the B-type GPCRs that have not been deorphanized in insects, there is one that appears to be the best candidate. This group of receptors is characterized by the B3 receptor from Bombyx (Yamanaka et al, 2008 ) and the receptor identified as 72 from Tribolium (Hauser et al, 2008 ) and corresponds to cluster A of Cardoso et al ( 2014 ). We thus looked for homologs of this receptor in other arthropod genomes and found such receptors only in those species that also have a calcitonin gene.…”
Section: Resultsmentioning
confidence: 99%
“…6B), providing evidence for the expected parallel coevolution of ligandreceptor pairs. A recent evaluation of family B GPCRs in the genomes of various invertebrate species revealed putative receptors in insects and nematodes that align with a subgroup of human family B GPCRs comprised of the PTHR1 along with the receptors for secretin and glucagon; the findings would thus suggest that PTH receptors originated before the protostome-deuterostome divergence that is estimated to have occurred about 1000 million years ago (Cardoso et al, 2014).…”
Section: Evolution Of Parathyroid Hormone Receptors and Their Ligmentioning
confidence: 99%